AVALIAÃ‡ÃƒO DA INFESTAÃ‡ÃƒO POR Singhiella simplex (HEMIPTERA: ALEYRODIDAE) EM Ficus benjamina NO MUNICÃPIO DE SÃƒO PAULO, SP, BRASIL - Velasco, Giuliana Del Nero; Moura, RogÃ©rio Goularte; Berti Filho, Evoneo; Couto, Hilton Thadeu Zarate do (REVISTA DE AGRICULTURA, 2016)
AVALIAÃ‡ÃƒO DA INFESTAÃ‡ÃƒO POR Singhiella simplex (HEMIPTERA: ALEYRODIDAE) EM Ficus benjamina NO MUNICÃPIO DE SÃƒO PAULO, SP, BRASIL